Clinical grading of Intrahepatic Cholestasis Pregnancy - Meena Pradhan; Yong SHAO (Journal of Nepal Medical Association, 2013)
Intrahepatic cholestasis of pregnancy (ICP) is the pregnancy induced liver disorder causing intense itching of palm, sole or even whole body especially in the evening at late second and third trimester. This disease categorized into mild and severe ICP according to raised level of LFT including serum level of Bile acid and Cholic acid. ICP has less morbidity to mother but significant risk for fetus in uterus. The predisposing element to cause intense pruritus is because of high amount of bile acid in maternal serum. Toxic bile acids affect fetal cardiomyocytes that retained in fetus body causing sudden intrauterine fetal death. ICP is commonly found in winter months and mostly itching of body occurs in the evening after sunset. Fetus in uterus is unsafe if mother’s bile acid exceeds normal value. ICP is successfully treated with Ursodeoxycholic acid (UDCA), S-adenosyl methionine (SAME), Dexamethasone and vitamin K.